MATTERS OF ENSURING MACROECONOMIC STABILITY IN ENHANCING THE ECONOMIC SECURITY OF THE AGRICULTURAL RESOURCES MARKET (World Economics and Finance Bulletin, 2025)
This article theoretically and practically examines issues such as improving relationships that serve to enhance the economic security of the agro-resource market operating within the country's agricultural sector and ensure macroeconomic stability
Keywords: agrarian market; market of agricultural resources; market of agricultural services